R.E.F.L.E.C.T: enhancing Vietnamese EFL undergraduates’ pronunciation proficiency - Ton Nu My Nhat; Hoang Thi Thu Hien (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract This research explores the use of reflective writing as a pedagogical tool to support Vietnamese EFL tertiary-level learners in improving their English pronunciation by gaining deeper insights into their individual learning experiences. Using an explanatory mixed-methods design, the study involved 94 English-major undergraduates. The quantitative dataset comprised students’ pretest and posttest scores, used to measure their pronunciation proficiency and evaluate the impact of reflective writing on specific aspects of pronunciation: accuracy, sentence stress, intonation, and aspects of connected speech (including rhythm, elision, and linking). The qualitative dataset included the learners’ reflective writings, analyzed thematically to identify pronunciation challenges, learners’ attitudes towards English pronunciation development, the influence of instructional approaches, the role of social and educational contexts, and the resources available for learning. Learners also voiced suggestions for improving pronunciation in an EFL context. Results confirm that reflective writing positively impacts learning outcomes, fostering improved pronunciation and promoting learners’ active engagement in their educational environment. The study introduces the R.E.F.L.E.C.T framework (Realization, Empowerment, Facilitation, Learning, Enhancement, Critical Thinking, and Transformation) to underscore the key values of reflection in higher education. While grounded in the Vietnamese EFL context, the findings contribute to the international literature on reflective practices, particularly in teaching and learning English pronunciation among EFL/ESL learners.